2020
DOI: 10.1016/j.mehy.2020.109755
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine as a drug to mitigate the effects of COVID-19

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 10 publications
0
31
0
2
Order By: Relevance
“…Podophyllotoxin is highly active against HIV and human papillomavirus (HPV) in vitro (Hensel et al, 2020). Amantadine and acyclovir, as antiviral agents, are also predicted to treat COVID-19, and amantadine has shown therapeutic effects in other studies on COVID-19 treatment (Aranda Abreu et al, 2020;Brenner, 2020;Rejdak and Grieb, 2020). However, the therapeutic effects of candidate drugs identified by Cmap predictions must be further investigated to generate empirical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Podophyllotoxin is highly active against HIV and human papillomavirus (HPV) in vitro (Hensel et al, 2020). Amantadine and acyclovir, as antiviral agents, are also predicted to treat COVID-19, and amantadine has shown therapeutic effects in other studies on COVID-19 treatment (Aranda Abreu et al, 2020;Brenner, 2020;Rejdak and Grieb, 2020). However, the therapeutic effects of candidate drugs identified by Cmap predictions must be further investigated to generate empirical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Adamantanes (i.e. amantadine, rimantadine) are thought to disrupt lysosomal trafficking, thereby impeding the release of SARS-CoV-2 ribonucleic acid (RNA) into the cell (Araújo et al, 2020[ 2 ]), and by inhibiting conductance of the envelope (E) protein (Aranda Abreu et al, 2020[ 1 ]). Acyclovir, a nucleotide analog antiviral, was found as a candidate drug for COVID-19 by potentially counteracting gene expression changes observed after SARS-CoV-2 infection (Li and Yang, 2020[ 16 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular docking studies have shown that amantadine could enter the SARS-Cov-2 E-channel and interfere with the release of its viral content into the cell, thus inhibiting its propagation [ 12 ]. Other studies have shown that amantadine as a treatment for COVID-19 infection has been effective, and the patients have recovered successfully, without the necessity to go to a hospital [ 13 ].…”
Section: Introductionmentioning
confidence: 99%